Assessment of climate change impact on high flows in a watershed characterized by flood regulating reservoirs - Shrestha, Sabin; Sharma, Suresh (International Journal of Agricultural and Biological Engineering, 2021)
A climate-induced extreme flow event such as flooding is one of the most devastating natural hazards, which can significantly damage human lives and properties. This study examined the effects of climate change on the high flow conditions in the Great Miami River Watershed in Ohio under two emission scenarios (RCP 4.5 and RCP 8.5). Streamflow for the 21st century was simulated by utilizing a watershed model - SWAT (Soil and Water Assessment Tool) and 10 different climate outputs from the Coupled Model Intercomparison Project phase 5 (CMIP5). The future streamflow was divided into three equal periods: 2016-2043 (early century), 2044-2071 (mid-century), and 2072-2099 (late century) and independently analyzed to compare high flows of respective intervals with baseline periods (1988-2015). The analysis predicted that 7-day, 10-year high-flow (7Q10) would increase by 38% under RCP 4.5 and 44% under RCP 8.5. Similarly, the annual peak flows for study periods were predicted to increase by 26% under RCP 4.5 and 38% under RCP 8.5 from the base period. However, the analysis demonstrated an erratic response for monthly peaks indicating that the peak flow would increase in summer months - May and July to October. Meanwhile, the result did not show any significant increase during the winter season, especially from November to April. The analysis of the four major dams located in the watershed showed that the dam’s peak discharges increase in January, May, and September. Even though increasing peaks were projected in September for the 21st century, the monthly peaks from the watershed outlet were found to be lowest in September as compared to other months. The frequency of future flooding compared to the historical record was found to be increasing in the mid-century under RCP 4.5 and the late century under RCP 8.5. As the future flood is projected to increase, this study finds the reasonable impact of climate change on flood regulating reservoirs/dams in monthly flows. However, daily high flows (90th percentile flow) would be increasing significantly (44% to 250%) under RCP 8.5.Keywords: climate change, high flows, SWAT, Great Miami River Watershed, flood regulating reservoir, assessmentDOI: 10.25165/j.ijabe.20211401.5883Citation: Shrestha S, Sharma S. Assessment of climate change impact on high flows in a watershed characterized by flood regulating reservoirs. Int J Agric & Biol Eng, 2021; 14(1): 178–191.